Can there be wrongful life at the end of life?: German courts revisit an old problem in a new context - Pfeifer, Ulrich; Horn, Ruth (Journal of medical ethics, 2020)
This article discusses a recent ruling by the German Federal Court concerning medical professional liability due to potentially unlawful clinically assisted nutrition and hydration (CANH) at the end of life. This case raises important ethical and legal questions regarding a third person’s right to judge the value of another person’s life and the concept of ’wrongful life’. In our brief report, we discuss the concepts of the ’value of life’ and wrongful life, which were evoked by the court, and how these concepts apply to the present case. We examine whether and to what extent value-o f-life judgements can be avoided in medical decision-m aking. The wrongful-life concept is crucial to the understanding of this case. It deals with the question whether life, even when suffering is involved, could ever be worse than death. The effects of this ruling on medical and legal practice in Germany are to be seen. It seems likely that it will discourage claims for compensation following life-s ustaining treatment (LST). However, it is unclear to what extent physicians’ decisions will be affected, especially those concerning withdrawal of CANH. We conclude that there is a risk that LST may come to be seen as the ’safe’ option for the physician, and hence, as always appropriate.